Effective photocatalytic and bifunctional electrocatalytic materials based on Keggin arsenomolybdates and different transition metal capped assemblies. Issue 25 (5th June 2018) - Li, Feng-rui; Lv, Jing-hua; Yu, Kai; Zhang, Mao-lin; Wang, Kun-peng; Meng, Fan-xue; Zhou, Bai-bin
Abstract : V, Co, and Cu were introduced into AsMo12 system to build three Keggin derivatives with different caps, which show excellent photocatalytic activity and bifunctional electrocatalytic behavior. Abstract : Three novel Keggin arsenomolybdates with transition metal modifying caps, (Hbimb)(H2 bimb)[AsMoVI8VV4Co2 O40 ] (1 ), (Hbimb)2 (H2 bimb)0.5 [AsMoVI8VV4Cu2 O40 ]·1.5H2 O (2 ), and [Cu I (imi)2 ][Cu I (imi)2 4 AsMoV6VVI6O40 (VIV2O2 )] (3 ) (bimb = 1, 4-bis(imidazol-l-yl)butane; imi = imidazole), were obtained via altering the solution pH and the organic ligands in the reaction system, and were characterized via routine techniques. Compounds1 and2 are tetra-vanadium substituted AsMoVI8VV4O40 clusters capped by two Co 2+ or Cu 2+ cations at two symmetrical pit positions of two opposite Mo4 O18 tetramers, and these represent the first tetra-vanadium substituted bi-cobalt(ii )/copper(ii ) capped assemblies. The basic unit of compound3 is one hexa-electron-reduced Keggin polyoxoanion AsMoV6MoVI6O40 capped by two VO5 units at the same positions. The adjacent basic units were bonded together via the square binuclear linker Cu2 (imi)4 O2 to yield an infinite 1D cap-to-cap chain, which was further aggregated together in A–B–A–B mode via a pair of Cu(1)(imi)2 linkers, forming an unique 2D layer. Compounds1–3 show bifunctional electrocatalytic character and effective photocatalytic performance toward the degradation of typical dyes under UV irradiation.